2017
DOI: 10.1007/s12034-016-1353-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high-surface-area spinel-type MgAl 2 O 4 nanoparticles by [Al(sal) 2 (H 2 O) 2 ] 2 [Mg(dipic) 2 ] and [Mg(H 2 O) 6 ][Al(ox) 2 (H 2 O) 2 ] 2 ⋅5H 2 O: influence of inorganic precursor type

Abstract: Spinel-type MgAl 2 O 4 nanoparticles with high surface area were synthesized by thermal decomposition of three different ion-pair complexes precursors, including [Mg(H 2 O) 6 ][Al(dipic) 2 ] 2 •6H 2 O, [Al(sal) 2 (H 2 O) 2 ] 2 [Mg(dipic) 2 ] and [Mg(H 2 O) 6 ][Al(ox) 2 (H 2 O) 2 ] 2 •5H 2 O. Influence of the inorganic precursor was investigated on synthesis and textural properties of magnesium aluminate nanopowders. The precursors [Mg(H 2 O) 6 ] [Al(dipic) 2 ] 2 •6H 2 O and [Al(sal) 2 (H 2 O) 2 ] 2 [Mg(dipic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The novel method was also compared with other different synthesis techniques-coprecipitation and citrate sol-gel-and the ion-pair complex precursor approach was reported to yield nanoparticles with the smallest crystallite size, maximum BET surface area, and lowest agglomeration degree. 136 In a follow-up study by the same group of researchers, 137 136 were compared. By comparing the spinel derived from the three different precursors, it was found that the [Al(sal) 2 (H 2 O) 2 ] 2 ⋅[Mg(dipic) 2 ] produced the maximum BET surface area and the lowest particle size.…”
Section: Synthesis Of Mas By Other Nonconventional Routesmentioning
confidence: 99%
See 2 more Smart Citations
“…The novel method was also compared with other different synthesis techniques-coprecipitation and citrate sol-gel-and the ion-pair complex precursor approach was reported to yield nanoparticles with the smallest crystallite size, maximum BET surface area, and lowest agglomeration degree. 136 In a follow-up study by the same group of researchers, 137 136 were compared. By comparing the spinel derived from the three different precursors, it was found that the [Al(sal) 2 (H 2 O) 2 ] 2 ⋅[Mg(dipic) 2 ] produced the maximum BET surface area and the lowest particle size.…”
Section: Synthesis Of Mas By Other Nonconventional Routesmentioning
confidence: 99%
“…By comparing the spinel derived from the three different precursors, it was found that the [Al(sal) 2 (H 2 O) 2 ] 2 ⋅[Mg(dipic) 2 ] produced the maximum BET surface area and the lowest particle size. 137…”
Section: Synthesis Of Mas By Other Nonconventional Routesmentioning
confidence: 99%
See 1 more Smart Citation